Location of Early Childhood Education in National Geographies: Indonesia, Nepal, Slovakia - Pupala, Branislav; Jose, Jomon (Indonesian Journal of Early Childhood Education Studies, 2021)
This paper offers a comparative analysis of early childhood education in three countries on two continents – Slovakia, Indonesia and Nepal. The analysis is based on long-term observations and research in ECEC in these countries. It shows that education mirrors culture, reflecting key aspects of it – physical, political, cultural and religious. Despite strong globalizing pressures to change and modernize, education is a localized phenomenon. ECEC is presented through its geographical contexts and geography of education is considered a suitable methodology for further research in ECEC. The article looks at how geographical characteristics shape education in the countries compared and briefly outlines the effect religious faith has on education in different countries and parts of the world.